Auditing in the Brazilian National Health System: the auditor's role in oral health services - Ayach, Carlos; Moimaz, Suzely Adas Saliba; Garbin, Cléa Adas Saliba (Saúde e Sociedade, 2013)
Auditing in health verifies processes and results in the provision of services, assuming the development of an adequate care model in accordance with the current legislation. In this research, the goal was to analyze the auditing activities within the Brazilian National Health System, in the oral health service, aiming to demonstrate the actions and their inclusion in the three governmental spheres. Documental analyses were undertaken, as well as literature reviews about auditing systems and the role of auditors in dental services since 1969. Results showed that six articles about dental auditing were found in the Brazilian National Health System and that the auditor's work is comprehensive in the management of the system - it consists of controlling, evaluating, supervising and providing guidance, and of ensuring both social participation and access to services. In oral health the auditor examines, monitors and supervises the planning of strategies and the procedures that were performed; performs the registration of professionals, Health Units and physical and budgetary programming; provides data for the information system and the payment of services rendered; supervises the compliance with the covenants, giving an educational approach rather than a police one to the resolution of problems. The conclusion is that there are few studies on dental auditing regarding the Brazilian National Health System and that the auditing system is a reliable administrative tool that is essential to managers in the development of health actions.